Putting the Critical Voice Aside - Religion, Politics, and Therapy As Described by Secular Therapists Working with Ultra-Orthodox Clients: A Qualitative Study from Israel - Doron, Einat (Journal of religion and health, 2026)
Israel's Ultra-Orthodox Jews (Haredi) are a culturally distinct and tightly-knit community. Since their lifestyle, which rests on the strict interpretation of religious sources, sets them as a cultural minority within the dominant secular culture of modern Israeli society, addressing mental health within this group requires tailored approaches that consider the community’s values and lifestyle, as well as the distinct social and political dynamics between secular therapists and Haredi clients. However, while Haredi's unique position often becomes a source of tension in Israeli politics and society, it also affects therapeutic encounters between ultra-orthodox clients and secular therapists, as this unique dynamic between religious and secular cultures can lead to ambivalent attitudes toward each other. This study was designed to examine the unique experiences of secular therapists in providing mental health treatment to the ultra-orthodox sector in Israel in the current social-political situation. Twenty-one qualitative semi-structured interviews conducted with secular psychologists and art therapists regarding their experiences with working with ultra-religious clients identified three main themes: (1) a feeling of an outsider, (2) colliding viewpoints, and (3) sameness. While interpretative phenomenological approach was used, the interviews were analysed using thematic analysis based on Colaizzi's approach. These themes highlight the ambivalent experience and illuminate this captivating intersection of therapy, religion, and society. Public workplaces should consider enabling intercultural therapies, acknowledging their benefits and challenges.